Two women talking in a crowded room - Unknown:::Creator::::::::::::
Photograph shows two women talking in a room with a small crowd of people in the background. The woman on the right is holding a light colored coat with what appears to be a fur collar. They are attending the 1973 YWCA annual meeting.